From aging to healthy aging - Patrick Kamphuis (Indonesian Nutrition Association, 2022)
“It’s not the years in the life, but the life in the years”. More and more people around the world are growing older than ever before, yet not everyone is doing so in good health. Nutrition is often an overlooked area of impact in helping older people maintain functional ability, as well as recover after moments of ill-health.